Sensitivity analysis in the selection of cogeneration systems with natural gas - Pineda León, Roberto (2008)
Having a general vision of cogeneration, its current and future status both in Peru and internationally would allow analyzing the alternatives for the development of this technology in the country, taking into account the current regulatory framework and the infrastructure conditions available on the use of natural gas with the purpose of diversifying the national energy matrix. Within this, sensitivity analysis is a tool that provides valuable elements about the feasibility of installing a specific Cogeneration system in the industry. The systemsCogeneration available today, are not only characterized by their important energy advantage and environmental, but also for being highly profitable investments. In the development of this work, a calculation methodology is shown to estimate the cogeneration potential of an industrial plant quickly, safely and reliably, using basic software designed in the MS Excel 2007 environment.